Ethnobotany of Limnocharis Flava (L.) Buch in Bakumpai Dayak Community of Bagus Village, Barito Kuala District as A Popular Scientific Book - Norhalisah, Norhalisah; Utami, Nurul Hidayati; Irianti, Riya (FKIP ULM, 2024)
Ethnobotany describes the relationship between plant benefits and communities over generations. Limnocharis flava (L.) Buch. is one of the plants utilized by Bakumpai Dayak community in Bagus Village and can be studied ethnobotanically. This research aims to describe the ethnobotanical study of Limnocharis flava (L.) Buch. in the Bakumpai Dayak community of Bagus Village, Barito Kuala District, and to determine the validity and readability of the content of the popular scientific book developed on the ethnobotany of genjer. This research used the development research method based on Plomp's model (1997) to develop teaching materials in the form of a popular scientific book. The results of this development research show six aspects/studies of genjer ethnobotany: genjer botanical study has a round stem (globosus), genjer ethno-pharmacological study as a remedy for tonsillitis and appetite enhancer supplement, genjer ethno-ecological study based on its growing conditions already meeting optimal conditions, genjer ethno-socioanthropological study as a complementary vegetable for wedding and celebration events, genjer ethno-economic study used as a mixture for raw vegetables and sold in markets, and genjer ethno-linguistic study named